Multi-criteria risk assessment approach for components risk ranking – The case study of an offshore wave energy converter. (April 2017) - Okoro, Uzoma; Kolios, Athanasios; Cui, Lin
Highlights: A new framework for condition-based risk assessment is developed. The fundamental risk criteria are decomposed to reduce uncertainty and increase reproducibility of the assessment. A list of generic failure modes is proposed with associated variables and parameters applicable to marine applications. The framework is applied on the real case study of a wave energy converter. Abstract: Experts' judgement is employed in offshore risk assessment because reliable failure data for quantitative risk analysis are scarce. The challenges with this practice lies with knowledge-based uncertainties which renders risk expression and estimation, hence components' risk-based prioritisation, subjective to the assessor – even for the same case study. In this paper, a new risk assessment framework is developed to improve the fidelity and consistency of prioritisation of components of complex offshore engineering systems based on expert judgement. Unlike other frameworks, such as the Failure Mode and Effect Criticality Analysis, it introduces two additional dimensions: variables and parameters, to allow more effective scoring. These additional dimensions provide the much needed and uniform information that will assist experts with the estimation of probability of occurrence, severity of consequence and safeguards, herein referred to as 3-D methodology. In so doing, it achieves a more systematic approach to risk description and estimation compared to the conventional Risk Priority Number (RPN) of FMECA. Finally, the framework is demonstrated on a real case study of a wave energy converter (WEC) and conclusions of the assessment proved well in comparison and prioritisation.